Guild structure in assemblages of forest macro-moths is maintained regardless of the level of anthropogenic disturbance - João Matos da Costa; Marcin Sielezniew (The European Zoological Journal)
Nowadays, almost all forest areas in temperate Europe are more or less affected by human activity. Nevertheless, recent studies show that anthropogenic habitat modifications should not be taken as negative from the outset. Lepidoptera, namely nocturnal macro-moths (Macroheterocera), are a key part of overall forest biodiversity. The ecology of these insects is relatively well understood, and due to how easy it is to attract and collect them, they have been the subject of many ecological studies. Macro-moth assemblages were sampled from May to September in 2018 and 2019, at nine sites representing four different biotope types, in a mosaic forest ecosystem in the Narew National Park (NE Poland). Three levels of anthropogenic pressure could be distinguished: alder forests (low level), planted pine forests (medium) and substitute communities of the two previous ones (higher). At each site two light Heath traps were simultaneously used, one with a 15W actinic light and the other with an 8W ultraviolet light. We found no differences in the proportion of generalist species among areas with different levels of anthropogenic disturbance, and the proportion of species classified according to their food plant type specificity was not significantly different among areas or study years. Regardless of the differences in moth diversity, there were similarities in the proportions of species between the areas over months and years. We registered no differences in proportions of species classified according to overwintering stages among areas, either. Our results revealed that the studied moth communities were characterized by certain general functional features independent of the level of anthropogenic disturbance.